Sheikh Mujibur Rahman : from rebel to founding father - Badrul Ahsan, Syed, 1954- (New Delhi : Niyogi Books, Pathak Shamabesh (Dhaka), 2014)
On Sheikh Mujibur Rahman, 1922-1975, founder of the nation of Bangladesh.
Includes index.
Donated by Akbar Ali Khan
Keywords: Mujibur Rahman, -- Sheikh, -- 1920-1975.; Politicians -- Bangladesh -- Biography; Ex-presidents -- Bangladesh -- Biography; Bangladesh -- Politics and government